Byzantium in the iconoclast era c. 680 - 850 a history. - Brubaker, Leslie; Haldon, John (Cambridge Cambridge university press, 2011)
"Iconoclasm, the debate about the legitimacy of religious art that began in Byzantium around 720 and continued for nearly 120 years, has long held a firm grip on the historical imagination. This is the first book in English for over fifty years to survey this most elusive and fascinating period in medieval history. It is also the first book in any language to combine the expertise of two authors who are specialists in the written, archaeological, and visual evidence from this period, a combination of particular importance to the iconoclasm debate. The authors have worked together to provide a comprehensive overview of the visual, written, and other materials that together help clarify the complex issues of iconoclasm in Byzantium. In doing so, they challenge many traditional assumptions about iconoclasm and set the period firmly in its broader political, cultural, and social-economic context"--Provided by publisher.
Belief, ideology, and practice in a changing world -- Leo III : iconoclast or opportunist? -- Constantine V and the institutionalisation of iconoclasm -- The triumph of tradition? The iconophile intermission, 775-813 -- The second iconoclasm -- Economy, society, and state -- Patterns of settlement : urban and rural life -- Social elites and the court -- Society, politics, and power -- Fiscal management and administration -- Strategic administration and the origins of the themata -- Iconoclasm, representation, and rewriting the past.
Keywords: Art and state -- Byzantine Empire -- History; Art, Byzantine -- History; Byzantine antiquities; Church and state -- Byzantine Empire -- History; Iconoclasm -- Byzantine Empire -- History; Iconoclasm -- Byzantine Empire -- History -- Sources; Icons, Byzantine; Byzantine Empire -- Church history; Byzantine Empire -- Church history -- Sources; Byzantine Empire -- Politics and government